The influence of impact surface on head kinematics and brain tissue response during impacts with equestrian helmets - Clark, J. M.; Connor, T. A.; Post, A.; Hoshizaki, T. B.; Gilchrist, M. D. (Sports Biomechanics, 2021)
Current equestrian standards employ a drop test to a rigid steel anvil. However, falls in equestrian sports often result in impacts with soft ground. The purpose of this study was to compare head kinematics and brain tissue response associated with surfaces impacted during equestrian accidents and corresponding helmet certification tests. A helmeted Hybrid III headform was dropped freely onto three different anvils (steel, turf and sand) at three impact locations. Peak linear acceleration, rotational acceleration and impact duration of the headform were measured. Resulting accelerations served as input into a three-dimensional finite element head model, which calculated Maximum principal strain (MPS) and von Mises stress (VMS) in the cerebrum. The results indicated that impacts to a steel anvil produced peak head kinematics and brain tissue responses that were two to three times greater than impacts against both turf and sand. Steel impacts were less than half the duration of turf and sand impacts. The observed response magnitudes obtained in this study suggest that equestrian helmet design should be improved, not only for impacts to rigid surfaces but also to compliant surfaces as response magnitudes for impacts to soft surfaces were still within the reported range for concussion in the literature.